Soil organic carbon regulation from chemistry in top- but microbial community in subsoil in eastern coastal China poplar plantations - Liu, Binchi; Xu, Xia; Xu, Chonghua; Ju, Chenghui; Guo, Liang; Li, Ning; Zhu, Zhu; Li, Qian; Shen, Caiqin; Cao, Guohua (Frontiers in Forests and Global Change, 2023)
Although patterns in the vertical distribution of soil organic carbon (SOC) are key to assessing soil C sequestration potential, they remain poorly understood. We sampled 18 soil profiles at one meter depth at the Dongtai Forest Farm to investigate the vertical distribution of SOC, the stoichiometric relationship between SOC and total nitrogen (TN) and the controlling factors of SOC at different soil depths. We found that SOC content decreased significantly with increasing soil depth. Approximately 67% of SOC was stored in the top 30 cm. The N-C scaling slope (i.e., the slope of the relationship between log-transformed N and C not significantly different from 1.0) revealed significant differences between top- and subsoil with N and C scaled isometrically in topsoil (0–30 cm), but not in subsoil (30–100 cm). SOC content was co-regulated by soil physiochemical and microbial properties at the site level with soil chemical and microbial properties dominant in the top- and subsoil, respectively. Topsoil SOC increased with soil TN, available phosphorus (AP) and fungal abundance. Subsoil SOC increased with the fungal-to-bacterial ratio, fungal abundance and soil dissoluble organic carbon (DOC). Our study highlights the dominance of microbial community in regulating SOC in the subsoil and advances our understanding of the variation in mechanisms regulating SOC along the soil profile.